The Land of Light, the Land of Shadow. About the Autobiographic Prose of Faruk Šehić - Bukwalt, Miłosz (Poznańskie Studia Slawistyczne, 2019)
This article is the first attempt in Poland to examine the following issues in The Book of Una, the novel by Faruk Šehić: the problems of autobiographic memory, war trauma, going through the trauma situation in a creation process (autobiography as a symbol of individual identity and an attempt to overcome the stressor). The analysis drew attention to the category of a journey into the depths of one’s self within the so-called past life regression present in the work by this Bosnian author. In the course of the examination, it was revealed that the intimate contact established by and between the protagonist with the important figures from his childhood, sentimental objects, the aquatic element, plant world and places of playing, adventure and shelter has a therapeutic dimension. The aforementioned issues were studied with the use of a set of scientific tools in the area of anthropology of culture (abjective experiences and objects, symbolism of blood, category of childhood), theory of trauma, hypnology and hyperesthesia, polemology, humanistic psychiatry, Bachelard’s theory of poetic image, topoanalysis and poetics of the elements. The process of interpretation also included the Jungian concept of structure of personality known as the Shadow archetype.